History Of The Organization And Development Of The Training System In Southern Uzbekistan (1952-1990) (Eurasian Journal of History, Geography and Economics, 2026)
This article discusses the history of the establishment and development of one of the most influential intellectual centers in southern Uzbekistan - the Kashkadarya Regional Institute for Advanced Training of Public Education Workers. In particular, the establishment of the educational institution in the city of Karshi, Kashkadarya region during the Soviet era, changes and problems in its life, and the state of its activities are analyzed based on scientific literature and archival sources.